2021
DOI: 10.3389/fanim.2021.622500
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and Fatty Acid Metabolism of Dairy Cows in a Total Mixed Ration or Pasture-Based System During Lactation

Abstract: In this study, we explored mechanisms related to glucose and fatty acid metabolism in Holstein–Friesian multiparous dairy cows during lactation under two feeding strategies. From 0 to 180 days postpartum, cows were fed total mixed ration (TMR) ad libitum (non-grazing group, G0) or grazed Festuca arundinacea or Medicago sativa and were supplemented with 5.4 kg DM/d of an energy-protein concentrate (grazing group, G1). From 180 to 250 days postpartum, all cows grazed F. arundinacea and were supplemented with TMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 95 publications
(121 reference statements)
4
13
1
Order By: Relevance
“…Negative energy balance markers such as plasma NEFA, plasma BHB, and liver triglyceride did not indicate subclinical ketosis (>1.0 mmol/L of plasma BHB) or clinical fatty liver (>10% liver triglyceride wet weight; Bobe et al, 2004;Meikle et al, 2004) and were similar to previously reported values for mid-to late lactation in grazing conditions (García-Roche et al, 2021). However, the NZH cows had greater plasma glucose concentrations than the NAH cows, probably due to greater glucose uptake by the mammary gland (Bell and Bauman, 1997), as milk yield in NAH cows was greater.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Negative energy balance markers such as plasma NEFA, plasma BHB, and liver triglyceride did not indicate subclinical ketosis (>1.0 mmol/L of plasma BHB) or clinical fatty liver (>10% liver triglyceride wet weight; Bobe et al, 2004;Meikle et al, 2004) and were similar to previously reported values for mid-to late lactation in grazing conditions (García-Roche et al, 2021). However, the NZH cows had greater plasma glucose concentrations than the NAH cows, probably due to greater glucose uptake by the mammary gland (Bell and Bauman, 1997), as milk yield in NAH cows was greater.…”
Section: Discussionsupporting
confidence: 87%
“…Plasma glucose, urea, BHB, and nonesterified fatty acids (NEFA) were determined spectrophotometrically with commercial kits from Biosystems S.A. for glucose and urea and from Randox Laboratories Ltd. for BHB and NEFA, at λ = 505 nm, 600 nm, 340 nm, and 560 nm, respectively (Astessiano et al, 2015;García-Roche et al, 2021).…”
Section: Plasma and Hepatic Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by the difference in physiological state; from a few days before calving to the fresh period, plasma BHB increases from incomplete oxidation of FA in the liver (Grummer, 2008), reducing the relative contribution of supplemental butyrate to overall plasma BHB. In the studies reporting that butyrate supplementation increased plasma BHB, cows were approximately 60 (Izumi et al, 2019), 150 (Halfen et al, 2021) or 180 DIM (Urrutia et al, 2019), when excessive FA mobilization likely did not occur (Grum et al, 1996;Nogalski et al, 2012;García-Roche et al, 2021) and BHB production in the liver was reduced, which increased the relative contribution of supplemental butyrate to plasma BHB.…”
Section: Effect Of Butyrate Supplementationmentioning
confidence: 99%
“…The authors used various analytical methods to decipher intermediary flux via metabolite measurements that reflected on biochemical reaction architectures. The diverse mitochondrial adaptation to TMR and pasture-based feeding was recently strengthened by genetic and protein expression experiments (García-Roche et al, 2021). These are clearly substantial advancements for the field to understand the significance of biochemical reactions required for the production of milk and other biosynthetic products in cattle fed either by grain or grass.…”
Section: Introductionmentioning
confidence: 99%